The external quality assessment scheme in coagulation: five years’ experience as a participating laboratory - Sapre, Jyoti Prakash; Chaudhari, Sanjay Namdev; Shah, Megha Pradipbhai (International Journal of Research in Medical Sciences, 2017)
Background:The attainment of quality services in a laboratory requires a comprehensive quality assurance programme which includes both internal and external quality control. External Quality Assessment Scheme (EQAS) programmes are accepted around the world as invaluable tools by laboratories to assess the performance of their testing systems. Results are objectively compared to other laboratories, using the same methodologies for every parameter. The goal of this study was to review EQAS results from time to time in an effort to improve the performance of the laboratory. Methods: Observational study done at Pramukhswami medical college, Shree Krishna hospital, Karamsad from January 2009 to December 2013. In the present study we have evaluated our EQAS test result of the past five years, from 2009 to 2013. We receive two samples in duplicate in lyophilised form, which are stored at 2-8°C in the refrigerator. The samples are reconstituted with 1 ml of distilled water at the time of procedure. The samples are received quarterly in a year. The test results of all the samples are analysed and documented. Results: Satisfactory results were obtained in all the cycles except four times. Discrepancy was observed in Prothrombin time INR (International Standardized Ratio). Root cause analysis was performed and necessary action taken. Conclusion:This participation in EQAS over the last five years has helped us significantly to improve our laboratory services in terms of performance evaluation, patient care and overall quality of laboratory practices.